Design of a tuition-online system and scalability performance improvement of sparse-mode multicast protocols - Xu, Sheng. (2008)
This thesis presents the design of a distance learning system and the study of the scalability improvement schemes for multicast protocols. Firstly, it gives a brief description of the motivation and current developments of distance learning system in the global workplace. Motivated by this trend, an interactive distance learning system, the Tuition-online, was designed based on duplicating the traditional classroom education model. ATM network was chosen as the underlying communication network to support high-speed multimedia data transmission. In the Tuition-online, besides downloading courseware, submitting homework assignments and contacting tutors using e-mail, a student could book a timeslot with a particular tutor and call the particular server at the specific time to have an interactive on-line tuition session with the tutor when he/she needs assistance on his/her studies. The overall software structure, the process modules, inter-process communication mechanism, security issues and major information data structure of the Tuition-online system was designed and implemented. Subsequently, some snapshots of the application are given and detailed description of system functions is introduced based on user usage need.